Evaluation of factors associated with recruitment rates in early phase clinical trials based on the European Clinical Trials Register data - Paloma Moraga Alapont; Paula Prieto; Mikel Urroz; María Jiménez; Antonio J. Carcas; Alberto M. Borobia (Clinical and Translational Science, 2023)
Abstract Effective participant recruitment is a critical challenge in clinical trials. Inadequate enrollment of participants can precipitate delays, escalated costs, and compromise scientific integrity. Despite its relevance, particularly during the early phases, it persists as an obstacle in the field of clinical research. The primary aim of this study was to analyze the recruitment rates of early‐phase clinical trials and evaluate their potential associations with key trial characteristics. Using a descriptive and statistical analysis, a research study was conducted based on the early‐phase trials registered at the European Clinical Trials Register (EU‐CTR), spanning the timeframe from January 2017 to December 2021. Among the 194 trials examined, we found median recruitment rates of 68%. A more detailed exploration revealed a greater level of success in terms of recruitment achievement in pediatric trials when compared to trials involving adults, non‐oncologic trials, or those also developed in non‐European countries. It is important to underscore that only 69 trials out of the total managed to conclude recruitment, with the most prevalent reason for premature cessation being the presence of efficacy and safety issues or sponsor's strategy. This number can be greatly improved. Despite certain disparities observed in the information within EU‐CTR, we have successfully determined the recruitment rates of the studies and established associations with some of the clinical trial characteristics analyzed. Owing to the inherent constraints of this study, further research is warranted to gain a comprehensive understanding of the intricate interplay between trial characteristics and their impact on recruitment rates in early‐phase studies.